425. The Utility of Paired Upper and Lower COVID-19 Sampling in Patients with Artificial Airways. (31st December 2020) - Kitt, Eimear; Sammons, Julia S; Chiotos, Kathleen; Coffin, Susan E; Coffin, Susan E; Ballantine, Allison; Gallagher, Elizabeth; Mojica, Coralee DelValle; O'Callaghan, Kevin P; Kerman, Caryn; Harris, Rebecca; Bell, Louis; et al.
Abstract: Background: The Centers for Disease Control and Prevention (CDC) recommends upper respiratory tract (URT) polymerase chain reaction (PCR) testing as the initial diagnostic test for Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Lower respiratory tract (LRT) testing for patients requiring mechanical ventilation is also recommended. The goal of this study was to evaluate concordance between paired URT and LRT specimens in children undergoing pre-admission/procedure screening or diagnostic testing. We hypothesized that < 10% of paired tests would have discordant results. Methods: Single center cross-sectional study including children with artificial airways who had paired URT and LRT SARS-CoV-2 PCR testing between 4/1/2020 and 6/8/2020. URT specimens included nasopharyngeal (NP) swabs and aspirates. LRT specimens included tracheal aspirates and bronchoalveolar lavages. URT and LRT specimens were classified as paired if the two specimens were collected within 24 hours. Artificial airways included tracheostomies and endotracheal tubes. Tests were classified as diagnostic versus screening based on the indication selected in the order. Results: 102 paired specimens were obtained during the study period. Fifty-nine were performed for screening and 43 were performed for diagnosis of suspected SARS-CoV-2. Overall, 94 specimens (92%) were concordant, including 89 negative from both sources and 5 positive from both sources. Eight specimens (8%) were discordant, all of which were positive from the URT and negative from the LRT (Figure 1). Among patients undergoing screening, 3 of 4 positive tests were discordant and among symptomatic patients, 5 of 9 positive tests were discordant. There were no instances of a positive LRT specimen with a negative URT specimen. Figure 1. Performance of upper and lower respiratory tract SARS-CoV-2 PCR testing in children with artificial airways Conclusion: Overall, most paired samples from the URT and LRT yielded concordant results with no pairs positive from the LRT and negative from the URT. These data support the CDC recommendation that URT specimens are the preferred initial SARS-CoV-2 test, while LRT specimens should be collected only from mechanically ventilated with suspected SARS-CoV-2. Disclosures: All Authors : No reported disclosures